2019
DOI: 10.1111/anu.13012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary docosahexaenoic acid on growth performance, fatty acid profile and lipogenesis of blunt snout bream ( Megalobrama amblycephala )

Abstract: Six diets were designed to investigate the effects of dietary docosahexaenoic acid (22:6n‐3; DHA) levels (0.5, 1.3, 2.3, 4.2, 8.1 and 15.9 g/kg diets) on growth performance, fatty acid profile and expression of some lipogenesis‐related genes of blunt snout bream (Megalobrama amblycephala). Fish (average weight: 26.40 ± 0.11 g) were randomly fed one of six diets for 8 weeks. Results indicated that the final body weight (FBW) and specific growth rate (SGR) of fish fed 1.3 g/kg DHA were significantly higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Docosahexaenoic acid (C22:6n-3; DHA) is an essential n-3 polyunsaturated fatty acid (n-3 PUFA) that is commonly used as a feeding supplement for aquatic animals (Hossain et al, 2012;Hong et al, 2017;Wang et al, 2019), pigs (Gabler et al, 2007;Li et al, 2009), chickens (Allen and Danforth, 1998;Howe et al, 2002), and other species. DHA is also an important health product for human use (Holub, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Docosahexaenoic acid (C22:6n-3; DHA) is an essential n-3 polyunsaturated fatty acid (n-3 PUFA) that is commonly used as a feeding supplement for aquatic animals (Hossain et al, 2012;Hong et al, 2017;Wang et al, 2019), pigs (Gabler et al, 2007;Li et al, 2009), chickens (Allen and Danforth, 1998;Howe et al, 2002), and other species. DHA is also an important health product for human use (Holub, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been very few studies focusing on the damage caused by unoxidized DHA. Our previous study found that a high level of DHA reduced growth performance, indicating that excessive DHA, not oxidized, may be harmful to fish growth (Wang et al, 2019). Investigating whether there is possible damage from high levels of unoxidized DHA is important for human and animal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Oil Red O staining results showed that hybrid grouper that were fed diets with lower DHA:EPA ratios (D/E 0.54 and 1.01) exhibited significantly higher lipid accumulation in the liver, which agreed with a study of Starry Flounder in which the group with the lowest dietary DHA:EPA ratio (D/E 0.64) had the highest liver lipid level (Ma et al 2014). Similarly, a study of Blunt Snout Bream Megalobrama amblycephala also found that liver lipid accumulation significantly increased in fish that were fed a diet containing DHA at 0.23 g/100 g, but it decreased in fish that received the high level of DHA (Wang et al 2020). Lipid deposition is related to the synthesis and oxidation rate, so we further explored how the dietary DHA:EPA ratio affected hepatic lipid metabolism through its impact on gene expression, including lipid synthesis and degradation.…”
Section: Discussionmentioning
confidence: 92%
“…The up-regulation of hepatic srebp-1 in fish fed the CB diet compared with CTRL could indicate optimal level of n-3 LC-PUFA for carp in the diet, since srebp-1, a major lipogenesis regulator, may both promote or decrease lipids biosynthesis depending on n-3 LC-PUFA intake and the ratio between EPA and DHA in feed (Minghetti et al, 2011;Jin et al, 2017;Wang et al, 2020). Furthermore, down-regulation of srebp-1 and its target gene fas in CTRL fed carp compared with eCTRL may suggest weakened lipogenesis related with inadequate DHA level in the feed mimicking a commercial blend.…”
Section: Lipids Metabolismmentioning
confidence: 99%